Patients with neuregulin 1 (NRG1) rearranged cancer are suitable for the theranostic approach and targeted therapy - Ondič, O; Ptáková, N; Janovský, V; Vančurová, J; Hósová, M; Michal, M; Pešek, M (Klinicka onkologie, 2022)
INTRODUCTION: Neuregulin 1 (NRG1) gene fusion was detected in a wide range of carcinomas. It is most frequently present in lung adenocarcinomas, especially in KRAS and BRAF wild-type cases. PURPOSE: We present a newly described diverse group of NRG1 rearranged carcinomas. The paper explains basic molecular principles associated with this oncogenic driver. It consists of ERBB3 (HER3) and ERBB2 (HER2) receptor activation with downstream activation of PIK and MAPK canonical pathways. The experience with new therapeutic modalities is summarized. CONCLUSIONS: So far, the global results of cytotoxic, immune and targeted therapies were dis-appointing. Further research (including two studies in Europe) is underway, developing new therapeutic strategies and examining this cancer bio-logy. In the meantime, it is possible to dia-gnose NRG1 rearranged carcinomas in the Czech Republic since mRNA next generation sequencing (NGS) analysis is readily available.
Keywords: individualizovaná medicína; adenokarcinom plic; neuregulin-1; Neoplasms; nádory plic; neuregulin 1; nádory; ERBB 3 protein; lidé; Antineoplastic Agents; protinádorové látky; Receptor, ErbB-2; receptor erbB-2; NRG 1 protein; Lung Neoplasms; molecular targeted therapy; Precision Medicine; solid tumors; molecular targeted therapies; Adenocarcinoma of Lung; Neuregulin-1; ERBB 2 protein; Humans